تعليم الاستماع باستخدام لعبة الهمس المتسلسلة في المدرسة الثانوية الإسلامية الحكومية 3 فيدي - Syarifah Rahmi; Zainal Abidin Hajib; Siti Hasanah (JURNAL AL-IHDA : Media Ilmiah Bahasa Arab, 2023)
The objectives of this research are to find out the process of teaching listening by using the sequential whispering game in the Islamic State Secondary School 3 Pidie, and to find out the extent of its effectiveness. The research methodology that the researcher used was the experimental research method, and to collect data, the researcher did observation and pre and post test. As for the results of the research, it is effective to improve the students' ability to listen to the students in the Islamic State Secondary School 3 Pidie. This is based on the test result - t 7,582 - greater than the result t - table which is 2,262 -..